2020
DOI: 10.1186/s13046-020-01757-x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular and gene/miRNA expression profiles of radioiodine resistant papillary thyroid cancer

Abstract: Background Papillary thyroid cancer (PTC) is the most frequent endocrine tumor. Radioiodine (RAI) treatment is highly effective in these tumors, but up to 60% of metastatic cases become RAI-refractory. Scanty data are available on either the molecular pattern of radioiodine refractory papillary thyroid cancers (PTC) or the mechanisms responsible for RAI resistance. Methods We analyzed the molecular profile and gene/miRNA expression in primary PTCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…PTC is known as a general endocrine cancer with excellent prognosis [ 35 , 36 ]. However, unfortunately, several studies have demonstrated that recurrent or metastatic PTC is refractory to most medical treatments [ 8 , 37 , 38 , 39 , 40 ]. Such refractory PTC is usually slothful; however, following anaplasia of the lesion, it becomes undifferentiated cancer that then expands quickly, leading to poor prognosis [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTC is known as a general endocrine cancer with excellent prognosis [ 35 , 36 ]. However, unfortunately, several studies have demonstrated that recurrent or metastatic PTC is refractory to most medical treatments [ 8 , 37 , 38 , 39 , 40 ]. Such refractory PTC is usually slothful; however, following anaplasia of the lesion, it becomes undifferentiated cancer that then expands quickly, leading to poor prognosis [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has to be emphasized that difference in terms of performance (specificity, sensitivity, accuracy) is comparable between these two classes of mining methods (simple and sophisticated). Therefore, in current biomarker research simple solutions such as NTP classifier became popular [ 125 , 126 ]. Moreover, sets of selected markers offer much better performance than single marker, therefore, currently in various studies predictive power have benefited from such multi-marker approach [ 127 ].…”
Section: Applications Of Transcriptome Analysis In Oncologymentioning
confidence: 99%
“…The sodium-iodide symporter (NIS) is a trans-membrane glycoprotein having 13 transmembrane domains that mediates the active uptake of each circulating iodide ion in exchange of 2 intracellular sodium ions by the thyroid gland ( 11 ). It has been found that RAI resistance is related to the abnormal depletion or decreased expression of NIS ( 12 , 13 ). Multiple mechanisms have been identified in connection to altered NIS expression in PTC patients, such as thyroid gland-specific transcription termination factor-1 (TTF1) and paired box gene-8 (PAX8)-mediated induction of thyroid-stimulating hormone (TSH), which in turn modulates NIS transcription ( 14 ).…”
Section: Introductionmentioning
confidence: 99%